Letter from Hugh S. Taylor to Max Bredig, November 22, 1939 - Taylor, Hugh S. (Hugh Stott) (1939)
Hugh S. Taylor (1890-1974) informs Max Bredig (1902-1977) that the Princeton University President, Harold Willis Dodds (1889-1980) is in the process of writing an offer letter for a two-year Research Associate position for Max's father, Georg Bredig (1868-1944).
Keywords: Bredig, Max Albert, 1902-1977; Taylor, Hugh S. (Hugh Stott), 1890-1974; Emigration and immigration; Princeton University